Development of a Web-Based Assessment of Pancasila Student Character in Senior High Schools - Salahuddin, Salahuddin; Erniati, Erniati; Mistiani, Wiwin; Gusnarib, Gusnarib; Ardiansyah, A. (Jurnal Pendidikan Progresif, 2025)
Development of Web-Based Assessment for Pancasila Student Character in Senior High Schools: This study aims to develop a web-based student character assessment system oriented toward the Pancasila Student Profile for the Senior High School level. The system integrates three assessment methods teacher assessment, peer assessment, and self-assessment to gather comprehensive and objective data about student character. The instrument used in this system is based on six core dimensions of the Pancasila Student Profile: faith and devotion to God Almighty, global diversity, cooperation, independence, critical reasoning, and creativity. Each dimension includes five indicators, resulting in 30 items in total. Instrument development followed the Orindo & Antonio (1984) model, while the web system design adopted principles from Martin & Betrus (2019), emphasizing digital efficiency and functional design. Research findings show the developed system is valid, reliable, and efficient. Content validity testing yielded an average Aiken’s index of 0.882, and construct validity was confirmed using Confirmatory Factor Analysis (CFA) with satisfactory model fit results (p ≥ 0.05; RMSEA ≤ 0.08; CFI, TLI, IFI ≥ 0.95; factor loadings > 0.3). All six dimensions showed Composite Reliability (CR) scores above 0.7, and Cronbach’s Alpha reached 0.859, indicating strong internal consistency.The system was built using PHP, HTML, CSS, JavaScript, and MySQL. Expert validation yielded an average Aiken’s index of 0.941, affirming its visual and functional quality. A practicality test with 50 teachers produced an average score of 86%, indicating the system is highly practical. Integration of multiple assessment types allows for data triangulation and comprehensive character evaluation. The system supports teachers in assessing and fostering character, simplifies the process, enhances transparency, and enables real-time data analysis, offering a scalable and effective digital solution for character education in Senior high schools. Keyword: web based assessment, character, pancasila student, EFA, CFA.